An In Vivo Model of Estrogen Supplementation Concerning the Expression of Ca2+-Dependent Exchangers and Mortality, Vitality and Survival After Myocardial Infarction in Ovariectomized Rats - Tomáš Toporcer; Tomáš Grendel; Ivana Špaková; Alžbeta Blichárová; Ľudmila Verbóová; Zuzana Benetinová; Beata Čižmárová; Miroslava Rabajdová; Silvia Toporcerová (Journal of Cardiovascular Development and Disease)
Background: Ischemic-reperfusion damage of cardiomyocytes due to myocardial infarction (MI) often leads to the death of an individual. Premenopausal women have been observed to have a significantly lower risk of cardiovascular disease (CVD) than men of the same age. In menopausal women, this trend is significantly reversed, and the risk of CVD increases up to 10-fold. Estrogens affect the development and function of the heart muscle, and as they decrease, the risk and poor prognosis of CVD increase. This study is focused on the effects of estrogen supplementation on morbidity, vitality, and NCX1 expression after MI on a model system. Methods: In this study, female Sprague Dawley rats (n = 58), which were divided into three experimental groups (NN—control group, non-supplemented; OVX-N—ovariectomized, non-supplemented; OVX-S—ovariectomized, supplemented), received left thoracotomy in the fourth intercostal space. The left anterior descendent coronary artery was ligated 2 mm from its origin with an 8.0 suture. An immunohistological analysis as well as an RT-PCR analysis of NCX1 expression were performed. Results: A higher survival rate was recorded in the OVX-N group (86%) in comparison with the OVX-S group (53%) (p < 0.05). In addition, higher NCX1 expression 7 days/14 days after MI in the OVX-S group in comparison with the NN and OVX-N (p < 0.001 and p < 0.05) groups was recorded. Seven days after MI, a significantly higher expression (p < 0.005) of mRNA NCX1 in the OVX-N group was also recorded in comparison with the NN group. Conclusions: This study provides a comprehensive description of the effect of estrogen supplementation on NCX1 expression and overall vitality in ovariectomized rats that survived MI.